The State Socialist Working Group of the 1950s and 1960s and its Interdisciplinary Aspects - Shuba, Aliaksandr (Opus Incertum, 2025)
This paper explores the trajectories of architectural and urban planning historiography within the state socialist countries of Central and Eastern Europe, focusing on the role of academic exchanges in shaping interdisciplinary methodologies. In the aftermath of the Second World War, the Soviet model influenced architectural practices and monument preservation across the USSR, the GDR, and other state socialist countries in Europe, embedding ideologically ‘correct’ rhetoric and Marxist materialist visions into historical narratives. A pivotal shift occurred in late 1954, when changes in Soviet architectural policy led to intensified criticism of architects and scholars, prompting widespread professional debates. In response, the international working group ‘History of Town Planning and Construction in Historical Cities’ (also known as the ‘Working Group’) was founded in 1955, facilitating discussions that sought to bridge the growing divide between architectural theory and practice. Through an analysis of contributions presented at the Erfurt, Warsaw, and Budapest conferences, this study examines how state socialist academics engaged with themes of urban development, preservation, and historical interpretation. Their debates not only revisited the role of aesthetics and Marxist materialism in architectural history but also created enduring and inherently interdisciplinary historiographical frameworks. By tracing the Working Group’s intellectual legacy, this study highlights its impact on both state socialist discourse and approaches to the history of architecture and urban planning.